The development of self-employment in Kazakhstan (ҚазҰУ хабаршысы. Экономика сериясы, 2017)
All dynamic processes in the employment sector of the Kazakhstan labor market requires reassessmentand revision of the structure of employment and the adoption of appropriate measures to fosteremployment, including self-employment in a market economy. These measures should ensure economicdevelopment of the country and at the same time to some extent, social protection of the population.In modern conditions, i.e. in the light of market economy development, economic relations, activitiesof the employed population in the Republic of Kazakhstan has created new types of employment orhas a new flexible forms of employment, of employment of people in the economic environment of thecountry. And one of these forms of employment – this self-employment. The phenomenon of self-employmentand its lack of theoretical research, regional feature development actualizes the content of thearticle. In a market economy, people adapt to the democratization, autonomy, and accordingly developtheir abilities by engaging in the field of entrepreneurship looking for sources of income in this area wasborn the self-employed. The article describes the main directions of development of self-employment inthe Kazakh labour market.